FEATURES OF YOUTH SLANG: LINGUISTIC, SOCIOCULTURAL, AND PRAGMATIC ASPECTS - Abdukarimova Charos; Asrorova Parizoda; Raxmatova Shaxrizoda; Abdakimova Zulxumor; Ahrorova Aziza (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the key features of youth slang as a dynamic and multifaceted linguistic phenomenon. The study focuses on its expressive, structural, sociocultural, and pragmatic characteristics, highlighting its role in identity construction and communication among young people. Special attention is given to lexical innovation, the influence of digital media, and the rapid evolution of slang. The analysis demonstrates that youth slang is not merely a deviation from standard language but an essential component of linguistic development reflecting broader social and cultural processes.